Sovereignty, Innovation, and Human Connection: The Foundations of a Renewed Partnership between France and Mongolia - Leveau, Arnaud (Mongolian Journal of Strategic Studies, 2025)
In an international environment increasingly characterised by overlapping geopolitical, ecological, and technological disruptions, often conceptualised as a condition of permacrisis, mid-sized and small states face growing constraints on their strategic autonomy. This article examines the evolving partnership between France and Mongolia as a case study in horizontal cooperation between non-hegemonic actors navigating structural vulnerability in Eurasia. Drawing on international relations theory, political economy, and climate governance scholarship, it argues that Franco–Mongolian cooperation is structured around a coherent trivoca: sovereignty and resilience, innovation and green transition, and human connectivity. Far from a symbolic bilateral relationship, this partnership reflects a shared strategic doctrine linking Mongolia’s “Third Neighbour” policy with France’s pursuit of European strategic autonomy. By analysing cooperation in cybersecurity, sustainable resource governance, renewable energy, and societal exchanges, particularly in the context of Mongolia’s hosting of COP17, the article demonstrates how such partnerships can enhance autonomy without provoking bloc alignment. The Franco–Mongolian case thus offers broader insights into how mid-sized powers can preserve agency and contribute to stability within an increasingly fragmented international order. Тусгаар тогтнол, инновац ба хүний харилцаа, холбоо: Франц, Монголын хоорондын шинэчлэгдсэн түншлэлийн үндэс Хураангуй Олон улсад жижиг, дунд улсууд геополитик,экологи, технологийн хөнөөлт байдалд буюу хямралт байдалд байгаа явдал нь стратегийн бие даасан байдалд сөрөг үр дагаварт хүргэх боллоо. Энэхүү өгүүлэлд Франц-Монголын хоорондын түншлэлийг Евроазийн бүтцийн эмзэг байдлыг даван туулахад хамтын хэвтээ ажиллагаагаар жишээ болгон авч үзсэн болно. Олон улсын харилцааны онол, улс төрийн эдийн засаг, уур амьсгалын засаглалын судалгаан дээр үндэслэн Франц-Монголын хамтын ажиллагааг тусгаар тогтнол ба сөрөн тэсвэрлэх, инновац ба ногоон шилжилт, хүний харилцаа, холбоо гэсэн бүтцийн хүрээнд судаллаа. Энэхүү түншлэлийг бэлгэдлийн хоёр талын харилцаанаас илүүтэйгээр Монголын “Гуравдагч хөрш”-ийн бодлогыг Францын Европын стратегийн бие даасан байдалтай холбосон стратегийн номлол гэж үзсэн. Кибер аюулгүй байдал, тогтвортой засаглал, сэргээгдэх эрчим хүч, нийгмийн солилцоо зэрэг хамтын ажиллагааг, нэн ялангуяа Монгол Улс COP 17-г зохион байгуулж байгаатай холбогдуулан шинжлэх, мөн энэхүү өгүүлэлээр хамтын бие даасан харилцааг эрчимжүүлэхэд чиглэгдсэнд оршино. Тиймээс Франц, Монгол зэрэг дунд гүрэн улам хуваагдмал болж буй олон улсын дэг журмын хүрээнд хэрхэн тогтвортой, эрх мэдэлтэй байх нь чухал юм. Түлхүүр үг : Стратегийн бие даасан байдал, Гуравлагч хөршийн бодлого, дунд гүрэн, хямралт байдал, Франц-Монголын харилцаа, сөрөн тэсвэрлэх; ногоон шилжилт